An epidemiological cross sectional study for screening of risk factors of diabetes using WHO STEPS guidelines in an urban slum of metropolitan city - Gohar, Meraj; Kazi, Yasmeen K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Diabetes is rapidly becoming one of the most common non communicable disease worldwide and its prevalence has increased. The risk factors associated with diabetes needs to be studied for its prevention and control. Methods: Study participants between the age group 25-64, at the community level were interviewed using the WHO steps questionnaire, which included their sociodemographic profile, history about their addiction, diet and physical activity. Their physical and biochemical measurements were also taken. Results: A total of 400 participants participated in the study. Out of this, 62.8% (251) were seen to be diabetic. Factors seen to be significantly associated with having the disease were age group 35-44 years, having education level above secondary, being unemployed, from nuclear family. Risk factors seen to be associated were being a smoker, having less than 5 servings of fruits, not doing physical activity, being obese and having hypercholesterolemia and hypertriglyceridemia. Conclusions: Prevention and control of diabetes needs to adopt an approach which aims at changing the lifestyle of individual. Healthier food choices, encouraging regular physical activity right from school level would definitely shape and influence long term behaviour.